Dignification of victims through exhumations in Colombia - Rios Oyola, Sandra Milena (Human rights review, 2021)
Exhumations aim to restore victims’ dignity because they constitute a step towards their individualisation and recognition as members not only of a particular family but of the human family. This article aims to contribute to the critical assessment of how the notion of human dignity and dignification are used in the context of mechanisms of transitional justice, such as exhumations. It focuses on the Colombian case from an interdisciplinary perspective based on socio-legal studies. The research is based on participant observation, interviews, and thematic analysis of the uses of the term dignity and dignification in the texts of the laws and protocols for the exhumations of victims of the armed conflict in Colombia. It explores two dimensions of dignification, which in turn contributes to the understanding of the complex relationship between victims, the state, and institutions of transitional justice.